The Amphibians of Mount Oku, Cameroon: an updated species inventory and conservation review - Doherty-Bone, Thomas M; Gvoždík, Václav (ZooKeys, 2017)
Amphibians are a disproportionately threatened group of vertebrates, the status of which in Sub-Saharan Africa is still uncertain, with heterogeneous fauna punctuated by mountains. Mount Oku, Cameroon is one such mountain, which holds many endemic and restricted-range species. The history of amphibian research on Mt Oku, current knowledge on biogeography and conservation biology is reviewed, including recent findings. This updated inventory adds 25 further species, with 50 species of amphibian so far recorded to the Oku Massif (c. 900 to 3,011 m). This includes 5 endemic to Mt Oku, 7 endemic to the Bamenda Highlands, 18 restricted to the highlands of Cameroon and Nigeria, and 20 with broader ranges across Africa. This includes a new mountain locality for the Critically Endangered Leptodactylodon axillaris. Among others, the first record of Phrynobatrachus schioetzi and Ptychadena taenioscelis from Cameroon are presented. The uncertainty of habitat affinities and elevational ranges are discussed. The proportion of threatened species on Mt Oku is 44.2%, but projected to increase to 47.9% due to new species descriptions and recent dramatic declines. The natural habitats of Mt Oku are irreplaceable refuges for its endemic and restricted-range amphibian populations under severe pressure elsewhere in their range. Threats to this important amphibian fauna are increasing, including agricultural encroachment, expanding aquaculture, livestock grazing, pollution, invasive species, forest loss and degradation. Past, present and desired conservation interventions to address these threats are discussed.
Keywords: Biodiversity; montane forests and grasslands; Central Africa; Cameroon Volcanic Line; caecilians; frogs; Lake Oku